2017
DOI: 10.1016/j.electacta.2017.09.138
|View full text |Cite
|
Sign up to set email alerts
|

In situ SR-XRD study of FeCO3 precipitation kinetics onto carbon steel in CO2-containing environments: The influence of brine pH

Abstract: The growth of iron carbonate (FeCO3) on the internal walls of carbon steel pipelines used for oil and gas transportation can reduce internal corrosion significantly. Solution pH can be considered as one of the most influential factors with regards to the kinetics, morphology and protection afforded by FeCO3 films. This paper presents results from a recently developed in situ Synchrotron Radiation-X-ray Diffraction (SR-XRD) flow cell integrated with electrochemistry for corrosion measurements. The cell was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 24 publications
4
55
0
Order By: Relevance
“…The coverage of the corrosion scale increased. Burkle 41 was also discussed the morphology and development of the FeCO 3 crystals over time. Burkle stated that the steel surface was almost entirely covered by FeCO 3 crystals aer several hours of exposure.…”
mentioning
confidence: 99%
“…The coverage of the corrosion scale increased. Burkle 41 was also discussed the morphology and development of the FeCO 3 crystals over time. Burkle stated that the steel surface was almost entirely covered by FeCO 3 crystals aer several hours of exposure.…”
mentioning
confidence: 99%
“…As shown in Figure , with the increase in Cl − concentration, the amount of FeCO 3 deposited on the steel surface decreased, and the crystalline character of FeCO 3 also weakened. Some studies have illustrated that the development and morphology of FeCO 3 crystals were closely related to solution pH. The decrease in solution pH considerably increased the solubility of Fe 2+ , resulting in slower precipitation and thus a decreased rate of surface coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Dugstad [ 4] suggested that a 'high degree' of super saturation is necessary in the bulk solution to obtain appreciable levels of FeCO3 formation on the steel sur face. However, more recent studies have indicated that enough sur face deposition to provide suppression of carbon steel corrosion rates can occur in systems with a bulk saturation below [2,[5][6][7].…”
Section: Understanding the Degree Of Pr Otection Afforded By The Layementioning
confidence: 99%
“…The ability of FeCO3 to achieve such a dramatic reduction in corrosion rate is believed to be achieved through a surface blocking effect as a result of the crystals being in direct contact with the steel substrate. However, it has also been suggested that the layer acts as a diffusion barrier to electrochemically active species involved in the cathodic reactions [2,3].…”
Section: Introductionmentioning
confidence: 99%